Featured topics in research on digital transformation: Evidence from a bibliometric study and content analysis - Facin, Ana Lucia Figueiredo [UNESP]; Barbosa, Ana Paula Franco Paes Leme; Matsumoto, Cristiane; Cruz, Ana Flavia Safady da Gama [UNESP]; Salerno, Mario Sergio (FapUNIFESP (SciELO), 2022)
Digital transformation (DT) arises in debates about trends in various industries, mainly in value creation through the innovation of products and services and how they are negotiated. DT poses new challenges to organizations, which this research aims to identify by answering: What is the structure of the literature on DT, and what themes have gained prominence in the last five years? This research conducted a systematic literature review with bibliometric analysis and content analysis. The bibliometric analysis highlighted the following discussions: strategic renewal amid DT; implementation of technologies in Industry 4.0; digitization to enable servitization; DT as an engine of innovation in business models; digital innovation management; and DT to change the consumer experience. The analyses point out avenues for further research and raise important questions for decision-makers in companies that want to reap the benefits of DT
Temas destacados en la investigación sobre transformación digital: Evidencia del estudio bibliométrico y análisis de contenido
TEMAS DE DESTAQUE NA PESQUISA EM TRANSFORMAÇÃO DIGITAL: EVIDÊNCIAS DE ESTUDO BIBLIOMÉTRICO E ANÁLISE DE CONTEÚDO
Keywords: Digital innovation; Digital platforms; Digital transformation; Digitization; Systematic review